Difference between revisions of "009B Sample Midterm 2, Problem 5"

From Math Wiki
Jump to navigation Jump to search
Line 7: Line 7:
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Foundations:    
 
!Foundations:    
|-
 
|Recall:
 
 
|-
 
|-
|'''1.''' <math style="vertical-align: -1px">\sec^2x=\tan^2x+1</math>
+
|'''1.''' Recall the trig identity
 
|-
 
|-
|'''2.''' <math style="vertical-align: -13px">\int \sec^2 x~dx=\tan x+C</math>
+
|&nbsp; &nbsp; &nbsp; &nbsp;<math style="vertical-align: -1px">\sec^2x=\tan^2x+1</math>
 
|-
 
|-
|How would you integrate <math style="vertical-align: -12px">\int \sec^2(x)\tan(x)~dx?</math>
+
|'''2.''' Recall
 +
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp;<math style="vertical-align: -13px">\int \sec^2 x~dx=\tan x+C</math>
 +
|-
 +
|'''3.''' How would you integrate &nbsp;<math style="vertical-align: -12px">\int \sec^2(x)\tan(x)~dx?</math>
 
|-
 
|-
 
|
 
|
::You could use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: -2px">u=\tan x.</math> Then, <math style="vertical-align: -5px">du=\sec^2(x)dx.</math> Thus,
+
&nbsp; &nbsp; &nbsp; &nbsp; You can use &nbsp;<math style="vertical-align: 0px">u</math>-substitution.  
 +
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp; Let &nbsp;<math style="vertical-align: -2px">u=\tan x.</math>  
 +
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp; Then, &nbsp;<math style="vertical-align: -5px">du=\sec^2(x)dx.</math>
 
|-
 
|-
 
|
 
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp; Thus,
 +
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{\int \sec^2(x)\tan(x)~dx} & = & \displaystyle{\int u~du}\\
 
\displaystyle{\int \sec^2(x)\tan(x)~dx} & = & \displaystyle{\int u~du}\\
 
&&\\
 
&&\\
 
& = & \displaystyle{\frac{u^2}{2}+C}\\
 
& = & \displaystyle{\frac{u^2}{2}+C}\\
 
&&\\
 
&&\\
& = & \displaystyle{\frac{\tan^2x}{2}+C.}\\
+
& = & \displaystyle{\frac{\tan^2x}{2}+C.}
 
\end{array}</math>
 
\end{array}</math>
 
|}
 
|}
Line 36: Line 44:
 
|First, we write  
 
|First, we write  
 
|-
 
|-
|
+
|&nbsp; &nbsp; &nbsp; &nbsp; <math style="vertical-align: -13px">\int \tan^4(x)~dx=\int \tan^2(x) \tan^2(x)~dx.</math>
::<math style="vertical-align: -13px">\int \tan^4(x)~dx=\int \tan^2(x) \tan^2(x)~dx.</math>
+
|-
 +
|Using the trig identity &nbsp;<math style="vertical-align: -5px">\sec^2(x)=\tan^2(x)+1,</math>  
 
|-
 
|-
|Using the trig identity <math style="vertical-align: -5px">\sec^2(x)=\tan^2(x)+1,</math> we have  
+
|we have  
 
|-
 
|-
|
+
|&nbsp; &nbsp; &nbsp; &nbsp;<math style="vertical-align: -5px">\tan^2(x)=\sec^2(x)-1.</math>
::<math style="vertical-align: -5px">\tan^2(x)=\sec^2(x)-1.</math>
 
 
|-
 
|-
|Plugging in the last identity into one of the <math style="vertical-align: -5px">\tan^2(x),</math> we get
+
|Plugging in the last identity into one of the &nbsp;<math style="vertical-align: -5px">\tan^2(x),</math>&nbsp; we get
 
|-
 
|-
|
+
|  
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{\int \tan^4(x)~dx} & = & \displaystyle{\int \tan^2(x) (\sec^2(x)-1)~dx}\\
 
\displaystyle{\int \tan^4(x)~dx} & = & \displaystyle{\int \tan^2(x) (\sec^2(x)-1)~dx}\\
 
&&\\
 
&&\\
 
& = & \displaystyle{\int \tan^2(x)\sec^2(x)~dx-\int \tan^2(x)~dx}\\
 
& = & \displaystyle{\int \tan^2(x)\sec^2(x)~dx-\int \tan^2(x)~dx}\\
 
&&\\
 
&&\\
& = & \displaystyle{\int \tan^2(x)\sec^2(x)~dx-\int (\sec^2x-1)~dx.}\\
+
& = & \displaystyle{\int \tan^2(x)\sec^2(x)~dx-\int (\sec^2x-1)~dx}
 
\end{array}</math>
 
\end{array}</math>
 
|-
 
|-
|using the identity again on the last equality.
+
|by using the identity again on the last equality.
 
|}
 
|}
  
Line 63: Line 71:
 
|So, we have  
 
|So, we have  
 
|-
 
|-
|
+
|&nbsp; &nbsp; &nbsp; &nbsp; <math style="vertical-align: -13px">\int \tan^4(x)~dx=\int \tan^2(x)\sec^2(x)~dx-\int (\sec^2x-1)~dx.</math>
::<math style="vertical-align: -13px">\int \tan^4(x)~dx=\int \tan^2(x)\sec^2(x)~dx-\int (\sec^2x-1)~dx.</math>
+
|-
 +
|For the first integral, we need to use &nbsp;<math style="vertical-align: 0px">u</math>-substitution.
 +
|-
 +
|Let &nbsp;<math style="vertical-align: -5px">u=\tan(x).</math>  
 
|-
 
|-
|For the first integral, we need to use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: -5px">u=\tan(x).</math> Then, <math style="vertical-align: -5px">du=\sec^2(x)dx.</math>
+
|Then, &nbsp;<math style="vertical-align: -5px">du=\sec^2(x)dx.</math>
 
|-
 
|-
 
|So, we have
 
|So, we have
 
|-
 
|-
|
+
| &nbsp; &nbsp; &nbsp; &nbsp; <math style="vertical-align: -13px">\int \tan^4(x)~dx=\int u^2~du-\int (\sec^2(x)-1)~dx.</math>
::<math style="vertical-align: -13px">\int \tan^4(x)~dx=\int u^2~du-\int (\sec^2(x)-1)~dx.</math>
 
 
|}
 
|}
  
Line 80: Line 90:
 
|-
 
|-
 
|  
 
|  
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{\int \tan^4(x)~dx} & = & \displaystyle{\frac{u^3}{3}-(\tan(x)-x)+C}\\
 
\displaystyle{\int \tan^4(x)~dx} & = & \displaystyle{\frac{u^3}{3}-(\tan(x)-x)+C}\\
 
&&\\
 
&&\\
& = & \displaystyle{\frac{\tan^3(x)}{3}-\tan(x)+x+C.}\\
+
& = & \displaystyle{\frac{\tan^3(x)}{3}-\tan(x)+x+C.}
 
\end{array}</math>
 
\end{array}</math>
 
|}
 
|}
 +
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Final Answer: &nbsp;  
 
!Final Answer: &nbsp;  
 
|-
 
|-
| &nbsp;&nbsp; <math>\frac{\tan^3(x)}{3}-\tan(x)+x+C</math>
+
| &nbsp; &nbsp; &nbsp; &nbsp; <math>\frac{\tan^3(x)}{3}-\tan(x)+x+C</math>
 
|}
 
|}
 
[[009B_Sample_Midterm_2|'''<u>Return to Sample Exam</u>''']]
 
[[009B_Sample_Midterm_2|'''<u>Return to Sample Exam</u>''']]

Revision as of 11:16, 9 April 2017

Evaluate the integral:


Foundations:  
1. Recall the trig identity
       
2. Recall
       
3. How would you integrate  

        You can use  -substitution.

        Let  
        Then,  

        Thus,

       


Solution:

Step 1:  
First, we write
       
Using the trig identity  
we have
       
Plugging in the last identity into one of the    we get

       

by using the identity again on the last equality.
Step 2:  
So, we have
       
For the first integral, we need to use  -substitution.
Let  
Then,  
So, we have
       
Step 3:  
We integrate to get

       


Final Answer:  
       

Return to Sample Exam